Antecedents of Career Decision-Making Self-Efficacy and its Impact on Job Satisfaction : A Study in the Indian IT Industry - Kishor Gedam, Rachna; Mehta, Nikhil; Date, Hema (Prabandhan: Indian Journal of Management, 2022)
Career decision-making among youth has been a buzzword. Making a career decision is one of the most critical tasks in an individual’ s life. Making a career choice and career changes in today’s uncertain work environment demands the ability to make informed career decisions. Many factors are essential in determining an individual’ s career and predicting the desired outcome. The IT industry is well-known for its high-quality structures and software companies (Kumari, 2022). This paper explored the process of career decision-making of IT professionals. The present study investigated the impact of personal and social factors on an individual’ s career decisions. Convenience sampling was used for data collection through a survey of 792 respondents from Tier-I and Tier-II cities of India through hybrid mode (online and physical). As a result of testing the hypotheses using the SPSS 26 and Smart PLS algorithm, 10 of the 16 hypotheses were found to be statistically significant, depicting that individual characteristics played a crucial role in making a career choice. At the same time, the impact of social support was found to be insignificant in today’ s contemporary and dynamic workplace due to individual proactive and self-reliant abilities.